Optimization of feeding frequency on the growth performance of thai pangas, Pangasius hypophthalmus (Sauvage, 1878) (Dhaka University Journal of Biological Sciences, 2015)
Thai pangas, Pangasius hypophthalmus fingerlings were reared for 60 days in laboratory condition to investigate the effects of feeding frequency on the growth performance. The fish fingerlings in three treatments were fed with two, three and four times a day, respectively. During the feeding trial, growth and feed utilization were assessed by condition factor (K), average daily gain (ADG), specific growth rate (SGR) and feed conversion ratio (FCR). Significantly lower FCR 1.81 ± 0.02 and higher ADG 0.38 ± 0.02 and SGR 2.20 ± 0.02% were found in fish fed thrice a day than that of other treatments (p < 0.05). Highest condition factor 1.69 ± 0.13 was found in fish fed four times a day while the lowest condition factor 0.77 ± 0.03 was detected in fish fed twice a day. Moisture content of Thai pangas in treatment T1, T2 and T3 were 79.23 ± 0.77, 78.08 ± 0.85 and 77.84 ± 0.17%, respectively. The crude protein, crude lipid and ash contents were 16.11 ± 0.00 to 16.38 ± 0.08%, 3.22 ± 0.27 to 3.41 ± 0.06% and 1.47 ± 0.02 to 1.82 ± 0.04%, respectively. The findings of the present study demonstrated that three times feeding frequency showed better growth performance and nutritional composition of Thai pangas fingerlings.Dhaka Univ. J. Biol. Sci. 24(1): 83-90, 2015 (January)